2011
DOI: 10.1177/0305735610388897
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better understanding of the relation between music preference, listening behavior, and personality

Abstract: Previous research relating personality and music preferences has often measured such reported preferences according to genre labels. To support previous research, the current paper has expanded investigation of the relation between personality and music preferences to include direct measurement of music listening behavior. A study (N = 395) measured participants' personality, reported music preferences, and their listening behavior, which was tracked while using a music database for a minimum period of three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
115
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 16 publications
17
115
2
1
Order By: Relevance
“…Personality may also be related to music preference, which could influence who chooses music video games versus classical instrumental music. For example, one study showed that listening to classical music predicted higher levels of neuroticism (Dunn, de Ruyter, & Bouwhuis, 2012), whereas another study showed that higher levels of conscientiousness were related to music preferences for songs that were upbeat and conventional (Rentfrow & Gosling, 2003). Our findings may have implications for understanding how personality interacts with music training effects, because we observed similar enhancements of musical listening skills for musicians and gamers, despite their contrasting personality profiles.…”
Section: Discussionmentioning
confidence: 57%
“…Personality may also be related to music preference, which could influence who chooses music video games versus classical instrumental music. For example, one study showed that listening to classical music predicted higher levels of neuroticism (Dunn, de Ruyter, & Bouwhuis, 2012), whereas another study showed that higher levels of conscientiousness were related to music preferences for songs that were upbeat and conventional (Rentfrow & Gosling, 2003). Our findings may have implications for understanding how personality interacts with music training effects, because we observed similar enhancements of musical listening skills for musicians and gamers, despite their contrasting personality profiles.…”
Section: Discussionmentioning
confidence: 57%
“…As recent research shows (see Rentfrow & Gosling, 2003;Colley, 2008;SchĂ€fer & Sedlmeier, 2009;Dunn, 2012;George et al, 2007;Leung & Kier, 2008), there have been numerous ways that types and genres of music have been defined, classified, and categorized. However, despite the subtle differences within the extant literature there does appear to be a considerable degree of convergence, with several robust music-preference factors emerging that are very similar (Rentfrow & Gosling, 2003).…”
Section: Why Investigate Music Preferences?mentioning
confidence: 99%
“…1, 2015 83 characteristics and traits. The correlations between musical preferences and psychological constructs such as personality traits (Rentfrow & Gosling, 2003), values (Boer et al, 2011 and age demographics (Bonneville-Roussy et al, 2013) have been studied, and convergence across many studies from varied geographical regions (Rentfrow & Gosling, 2003;George, Stickle, Rachid, & Wopnford, 2007;Delsing, ter Bogt, Engels, & Meeus, 2008;Zweigenhaft, 2008;Brown, 2012;Dunn, de Ruyter, & Bouwhuis, 2012;Langmeyer, Guglhör, & Tarnai, 2012) has provided clear evidence that these constructs are linked in a similar fashion. Extraverts for example prefer music that is "upbeat and conventional" (pop, soundtrack, and religious genres) and "energetic and rhythmic" (soul/funk and electronic/dance genres), and people high in Openness to Experience prefer "reflective and complex" music (blues, jazz, classical and folk genres) (Rentfrow & McDonald, 2009).…”
mentioning
confidence: 99%